SIMULATION OF A NEONATAL MONITOR FOR MEDICAL TRAINING PURPOSES (SIMULACIÓN DE UN MONITOR NEONATAL PARA ENTRENAMIENTO MÉDICO) (2013)
The design of a neonatal monitor for medical training purposes is hereby presented. In order to do that, the following main vital signs were modeled and simulated: ECG, pulse, blood pressure, CO2 level, among others. The signals were integrated to a graphic interface that generates different scenarios showing signals of patients with or without pathologies. Simulated signals were validated against real ones and, in general, the error is less than 5 %; in addition, the neonatal monitor was assessed by 16 specialists; those doctors stated that simulated signals are of “excellent quality”, “truthful” and that the interface is “user friendly”.Resumen: Se presenta el desarrollo de un monitor neonatal orientado al entrenamiento médico. Para esto se mo delaron y simularon los principales signos vitales como son: señal ECG, señal de pulso, presión arterial, nivel de CO2, entre otros. Las señales fueron integradas en una interfaz gráfica, la cual permite generar diferentes escenarios de pacientes, no solo normales sino también con patologías. Las señales simuladas fueron validadas contra señales reales y, en general, el error es inferior al 5 %. El monitor neonatal fue evaluado por 16 médicosespecialistas quienes manifestaron que las señales simuladas son “de excelente calidad”, “fidedignas” y que la interfaz es “amigable al usuario”.